Optimising the development impact of mineral resources extraction in Zimbabwe - Jourdan, Philip Paul (My University, 2015)
Zimbabwe has a rich and diverse minerals resource base that could be an important contributor to sustainable growth and development. The sector has rebounded dramatically from the hyperinflation economic crisis (2006-8) and with “dollarisation” (2009) the value of mineral production has increased six-fold to about $3 billion in 2011. However, if this increased mining activity is to ultimately result in more than just “holes-in-the-ground”, the crucial mineral linkages need to be realised whilst the resources are still extant. In order to optimise the economic linkages the current “colonial” minerals governance regime (“free mining”) needs to be fundamentally overhauled to both encourage the discovery of new mineral deposits and to maximise the developmental impact of known mineral assets through public tender against developmental outcomes. In this regard a Mineral Cadastre Information Management System (MCIMS) needs to be established as soon as possible. The current historically relatively high mineral prices (provoked by Asian demand) are likely to continue for the next couple of decades, so long as the major Asian economies (China and India) continue to display robust growth. Zimbabwe needs to take advantage of this widow of opportunity to use its finite mineral resources endowment to catalyse wider national economic growth and development through the maximisation of the seminal economic linkages. These are: Fiscal linkages- mineral resource rents must be captured, through the introduction of a resource rent tax, and reinvested into building long-term physical and human (knowledge) infrastructure, to underpin future national competitiveness, and into minerals development (exploration and technology development) to prolong the life of the minerals sector. Backward linkages – the minerals inputs sectors (capital goods, consumables, services) need to be grown, to take advantage of the expanding local demand, through measures to optimise the local content of mining purchases. The realisation of the backward linkages opportunities could seed wider industrialisation (capital goods) and economic transformation. Forward linkages – minerals could provide critical feedstocks into other job-creating sectors provided that they are beneficiated into appropriate intermediate products such as iron/steel, polymers and base metals for manufacturing; nitrogenous and phosphatic fertilisers for agriculture; cement, steel and copper for infrastructure and fossil fuels for power. However, mineral beneficiation often requires state facilitation through incentives and disincentives, such as a small export tax if the next value addition step is clearly viable. The use of PGM producer power, together with South Africa, should be explored to stimulate local value addition. Knowledge linkages – the maximisation of the minerals HRD and R&D opportunities is essential for realising the back- and forward linkages. No resource-based state has industrialised without significant investment in human and technology development. Joint strategies with the private sector should be pursued (PPPs), including the reinvestment of resource rents into knowledge development. Spatial linkages – high rent minerals are often able to finance major infrastructure (transport, power and water) which could underpin the development of other sectors such as agriculture, forestry and manufacturing, provided that the mineral leases provide for excess capacity and third party access at non-discriminatory prices. The huge Mwanesi iron ore resource could possibly underpin a low-cost logistics corridor to the coast which could substantially reduce national costs of trade (imports/exports). All of the linkages would be greatly enhanced through access to larger markets and in this regard configurations for equitable regional integration should be investigated and pursued (e.g. SADC and SACU). Zimbabwe’s minerals endowment could catalyse wider economic development if the minerals regime is overhauled and effectively administered to maximise all of the developmental opportunities associated with their extraction. This study formed the basis for the Draft Zimbabwe Minerals Development Policy (Appendix 7: Draft Zimbabwe Minerals Development Policy, page Error! Bookmark not defined.) currently under finalisation (MMMD).